Pengaruh Profitabilitas, Leverage, Kinerja Lingkungan Terhadap Pengungkapan Islamic Social Reporting (Studi Empiris pada Perusahaan yang Terdaftar di JII Tahun 2013-2017) - Kalbuana, Nawang; Sutadipraja, Marista Winanti; Purwanti, Titik; Santoso, Dwi (AKTSAR: Jurnal Akuntansi Syariah, 2019)
Islamic Social Reporting (ISR) is an index of social responsibility disclosure whose indicators are specific to the ethical principles of Islam. The purpose of this study is to analyze the effect of profitability, leverage and environmental performance on ISR disclosures on companies listed in the Jakarta Islamic Index (JII) during 2013-2017. In this study the magnitude of the ISR disclosure score that is filled with a company is obtained through annual reports using the content analysis method. Samples were selected by purposive sampling method. While hypothesis testing uses the method of multiple linear regression analysis. The results of this study indicate that the variable profitability, leverage and environmental performance simultaneously have a significant effect on ISR disclosure. While partially, profitability has no effect on ISR disclosure. Environmental performance and leverage have a positive and significant effect on ISR disclosure. The implications of this study are expected to be able to provide theoretical contributions related to the disclosure of Islamic social responsibility and practically useful to provide input to policy makers and regulators on the Indonesia Stock Exchange